2014
DOI: 10.1007/s00894-014-2536-6
|View full text |Cite
|
Sign up to set email alerts
|

The structure, stability, and electronic properties of ultra-thin BC2N nanotubes: a first-principles study

Abstract: Rapid developments of the silicon electronics industry have close to the physical limits and nanotube materials are the ideal materials to replace silicon for the preparation of next generation electronic devices. Boron-carbon-nitrogen nanotubes (BCNNT) can be formed by joining carbon nanotube (CNT) and boron nitride nanotube (BNNT) segments, and BC2N nanotubes have been widely and deeply studied. Here, we employed first-principles calculations based on density function theory (DFT) to study the structure, sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Among these, one (type I) showed metallic characteristics, whereas another (type II) was a semiconductor. In addition to this, other possible atomic arrangements and chemical compositions (BCN, B3C2N3, BC4N, and B5C2N5) of B − C − N tubular structures can also be found in the literature [9,18,20,26,37,42,43,60,68,75,77,86]. By virtue of these flexible electronic properties (from metallic to semiconducting), these materials have several potential applications such as electrical conductors [6,30,36,81], capacitors, light-emitting diodes, optical devices [6,18,29,30,55], and gas adsorption devices [7,33].…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Among these, one (type I) showed metallic characteristics, whereas another (type II) was a semiconductor. In addition to this, other possible atomic arrangements and chemical compositions (BCN, B3C2N3, BC4N, and B5C2N5) of B − C − N tubular structures can also be found in the literature [9,18,20,26,37,42,43,60,68,75,77,86]. By virtue of these flexible electronic properties (from metallic to semiconducting), these materials have several potential applications such as electrical conductors [6,30,36,81], capacitors, light-emitting diodes, optical devices [6,18,29,30,55], and gas adsorption devices [7,33].…”
Section: Introductionmentioning
confidence: 88%
“…These are: (i) stoichiometry, (ii) diameter, (iii) chirality, and (iv) atomic distribution of B, C, and N atoms in the hexagonal network. In light of the theoretical results for the same stoichiometry, BXCYNZ nanotubes can show different diameters, chiralities, and atomic arrangements [22,26,52,56,77,78]. That being said, some studies have indicated that the electronic band gap values can be altered according to nanotube chirality and diameter [26,55,56].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation